DEVELOPING POP-UP BOOK MEDIA TO INFLUENCE CHARACTER EDUCATION IN EARLY CHILDHOOD - Pelawi, Siti Alawiah Biastri; Pamungkas, Joko (Sekolah Tinggi Agama Islam Al Hidayah, 2025)
This study aims to obtain information about Pop-Up Book learning media that is suitable for instilling character education and to determine the effectiveness of Pop-Up Book learning media for early childhood. The Pop-Up Book learning media developed consists of animated images that display 6 character education (Religious, Tolerance, Discipline, Independent, Polite, and Caring). The type of research conducted is research and development (R&D) which refers to the ADDIE development model. The subjects in this study were 40 Class B students aged 5-6 years at Al Fatah Sedan Kindergarten Yogyakarta. The instruments used in this study were child assessment observation sheets, media expert validation assessment sheets, material expert validation assessment sheets, teacher response assessment sheets, and student response assessment sheets. The results of this study indicate that Pop-Up Book Learning Media for instilling character education according to material expert assessments reached a score of 92.19 with the category